Prevalence of hypertension and its determinants in an urbanized village of East Delhi - H., Raghavendra A.; Singh, Monika; Chabra, Pragti; Sharma, Arun Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is the major public health problem both in developing and developed nations. There is disparity in prevalence of hypertension in rural and urban areas. Data is available on the prevalence of hypertension in both urban and rural areas but studies on migratory population are limited. Methods: A community based cross sectional study conducted in urbanized village of east Delhi. WHO STEPS questionnaire was used collect the data. Total of 451 persons were interviewed by stratified random sampling method. Data analysis was done using SPSS version 16. Results: Prevalence of hypertension was 16.4%, high age group, high income, body mass index more than 23 and duration of stay in urban area were significantly associated with prevalence of hypertension. Conclusions: Older age group, higher BMI and longer duration of stay in urban area have significant associations with the higher prevalence of hypertension.